(untitled) (Private Law, 2025)
This research examines and analyzes legal issues concerning the decision to grant land rights in the Complete Systematic Land Registration (PTSL) with a focus on the Right of Use (Study of Decision No. 316/KTUN/2021). It explores the mechanism for granting individual land rights and rights of use through the PTSL program and seeks to understand the Supreme Court Judge’s reasoning in disputes involving double certificates (overlapping). The aim is to elucidate the mechanisms for granting individual land rights and rights of use, and to analyze the basis for the Supreme Court Judge’s considerations in the double certificate dispute (Overlapping) in Decision Number 316/KTUN/2021. This research is expected to contribute to the development of legal science and serve as a reference in the context of Complete Systematic Land Registration (PTSL). The research employs normative legal methods, applying statutory, conceptual, and case approach methodologies. The analysis reveals that the Panel of Judges in deciding Case Number 316/KTUN/2021 acted fairly by considering the principles of legal certainty and expediency. The Defendant failed to present a valid Decree as evidence during the trial and did not demonstrate the release of property rights, which is crucial in the context of transferring land rights. Consequently, the panel of judges upheld the Plaintiff’s claim and declared the disputed objects void by upholding the principle of Nemos Plus Iuris, which protects the actual right holder. The Defendant was not granted legal protection due to a lack of good faith and failure to apply the General Principles of Good Governance (AUPB) in issuing the contested objects.